Estimating the concentrations of some organophosphorus pesticides in the al-Bassel dam waters Safita-Syria (Latakia University Journal -Basic Sciences Series, 2019)
A mixture of Organophosphorus pesticides was detected in some areas of the Albasel Dam in Safita where the whole of the concentrations were of ng/L. The estuary of the Abrash River in the dam recorded the most widely distributed area of these pollutants, with a total value of the phosphorus pesticides 888.62 ng/L, followed by the Beit Sheikh  Yunus, which reached the total concentration of these pesticides 660.38 ng/L, while the total concentrations of these contaminants in the Aliazidia area 444.81 ng/L, and 250ng/L in the Sisneah region, which were the least contaminated by these pesticides. the most important compounds revealed are Phosdrin, Diazinon, Dichlorvos, Malathion, was also detected Methyl parathion compound which was prevented from use due to its risk and its carcinogenic effect to humans, particularly in the estuary of the Abrash River in the dam and area near the Beit of Sheikh Younis